K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 7 2017

bằng mấy cũng được

1) Ta có: \(\left(x+5\right)\left(x+2\right)-3\left(4x-3\right)=\left(5-x\right)^2\)

\(\Leftrightarrow x^2+2x+5x+10-12x+9=25-10x+x^2\)

\(\Leftrightarrow x^2-5x+19-25+10x-x^2=0\)

\(\Leftrightarrow5x-6=0\)

\(\Leftrightarrow5x=6\)

\(\Leftrightarrow x=\frac{6}{5}\)

Vậy: \(x=\frac{6}{5}\)

2) Ta có: \(\left(x+2\right)^3-\left(x-2\right)^3=12x\left(x-1\right)-8\)

\(\Leftrightarrow x^3+6x^2+12x+8-\left(x^3-6x^2+12x-8\right)=12x^2-12x-8\)

\(\Leftrightarrow x^3+6x^2+12x+8-x^3+6x^2-12x+8-12x^2+12x+8=0\)

\(\Leftrightarrow12x+24=0\)

\(\Leftrightarrow12x=-24\)

\(\Leftrightarrow x=-2\)

Vậy: x=-2

3) Ta có: \(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(\Leftrightarrow36x^2-12x-36x^2+27x-30=0\)

\(\Leftrightarrow15x-30=0\)

\(\Leftrightarrow15x=30\)

\(\Leftrightarrow x=2\)

Vậy: x=2

4) Ta có: \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)

\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x-81=0\)

\(\Leftrightarrow83x-83=0\)

\(\Leftrightarrow83x=83\)

\(\Leftrightarrow x=1\)

Vậy: x=1

21 tháng 9 2015

3x.(12x-4)-9x.(4x-3)=30

=> 36x2-12x-36x2+27x=30

=> 15x=30

=> x=30:15

=> x=2

21 tháng 8 2015

3x(12x-4)-9x(4x-3)=30

<=>36x2-12x-36x2+27x=30

<=>15x=30

<=>x=2

28 tháng 8 2017

\(3x.\left(12x-4\right)-9x.\left(4x-3\right)=30\)

\(36x^2-12x-36x^2=27x=30\)

\(15x=30\)

\(x=2\)

28 tháng 8 2017

\(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(\Rightarrow36x^2-12x-36x^2+27x=30\)

\(\Rightarrow\left(36x^2-36x^2\right)+\left(27x-12x\right)=30\)

\(\Rightarrow15x=30\)

\(\Rightarrow x=2\)

6 tháng 8 2016

\(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(36x^2-12x-36x^2+27x=30\)

\(15x=30\)

\(x=\frac{30}{15}\)

\(x=2\)

6 tháng 9 2017

\(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(36x^2-12x-36x^2+27x=30\)

\(15x=30\)

\(x=2\)

6 tháng 9 2017

Giải:

\(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(\Leftrightarrow36x^2-12x-36x^2+27x=30\)

\(\Leftrightarrow-12x+27x=30\)

\(\Leftrightarrow15x=30\)

\(\Leftrightarrow x=\dfrac{30}{15}\)

\(\Leftrightarrow x=2\)

Vậy \(x=2\).

Chúc bạn học tốt!!!

30 tháng 7 2015

 

3x (12x -4 )- 9x (4x-3)= 30 

<=>36x2-12x-36x3+27x=30

<=>15x=30

<=>x=2

 

3 tháng 7 2019

 3x(12x - 4 ) -9x (4x -3 ) = 30 
<=> 36x² - 12x - 36x²+27x = 30 
<=> 15x = 30 
<=> x=2

3 tháng 7 2019

\(3x\left(12x-4\right)-9.\left(4x-3\right)=30\)

\(=>36x^2-12x-36x^2+27x=30\)

\(=>15x=30\)

\(x=30:15=2\)

Vậy x = 2.

~ Hok tốt ~

30 tháng 9 2016

Ta có

  3x(12x-3)-9x(4x-4)=120

<=> 36x2-9x-36x2+36x=120

<=> 27x=120

   =>  x=40/9